The Use Of SQ3r Technique in Improving Students` Reading Comprehension - Amelia Biringkanae (Hasanuddin University, 2018)
Reading is one of the basic English skills which should be mastered by the students. This study was intended to explore the use of SQ3R technique to improve students` reading comprehension and to find out the students` perception toward the use of SQ3R technique. The method in this study is mixed method with Quan-qual model. The quantitative method used quasi-experimental design with control and experimental group. The population in this research used purposive sampling technique with the number of sample are 24 students as respondent; 12 students in control group and 12 students in experimental group. This study was conducted at SMP Negeri 2 Saluputti from the eighth grade students in academic year 2016/2017. The instrument that the writer used are reading test and questionnaire and the data were analyzed through SPSS 20. The research findings shows that the implementation of SQ3R technique could improve the students’ reading comprehension ability especially the eighth grade students of SMP Negeri 2 Saluputti and the eighth grade students of SMP Negeri 2 Saluputti have good perception towards the use of SQ3R technique. This research shows the improvement in students` reading comprehension, for that reason, it is recommended that the English teacher apply certain effective technique in teaching reading to enhance student`s comprehension.